2008
DOI: 10.1038/embor.2008.207
|View full text |Cite
|
Sign up to set email alerts
|

SHARP1/DEC2 inhibits adipogenic differentiation by regulating the activity of C/EBP

Abstract: SHARP1, a basic helix-loop-helix transcription factor, is expressed in many cell types; however, the mechanisms by which it regulates cellular differentiation remain largely unknown. Here, we show that SHARP1 negatively regulates adipogenesis. Although expression of the early marker CCAAT/enhancer binding protein b (C/EBPb) is not altered, its crucial downstream targets C/EBPa and peroxisome proliferator-activated receptor c (PPARc) are downregulated by SHARP1. Protein interaction studies confirm that SHARP1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…Although DEC1 prevents neither C/EBPβ nor RXR from binding to its target gene, DEC1 prevents bHLH domain containing transactivators such as BMAL1, MyoD and SREBP-1c, from binding to their target DNA by either protein-protein interaction or by directly binding to their responsive elements containing an E-box (Azmi et al, 2004;Choi et al, 2008;Li et al, 2004). Recently, Gulbagci et al demonstrated that DEC2, isoform of DEC1, also interacts with C/EBPβ and increases the recruitment of histone methyltransferase G9a to the promoter of PPARγ2 (Gulbagci et al, 2009). Our results suggested the fact that not only DEC2 but also DEC1 is involved in repression of PPARγ2 gene.…”
Section: Dec1 Is Recruited On the Promoter Of Pparγ2mentioning
confidence: 99%
“…Although DEC1 prevents neither C/EBPβ nor RXR from binding to its target gene, DEC1 prevents bHLH domain containing transactivators such as BMAL1, MyoD and SREBP-1c, from binding to their target DNA by either protein-protein interaction or by directly binding to their responsive elements containing an E-box (Azmi et al, 2004;Choi et al, 2008;Li et al, 2004). Recently, Gulbagci et al demonstrated that DEC2, isoform of DEC1, also interacts with C/EBPβ and increases the recruitment of histone methyltransferase G9a to the promoter of PPARγ2 (Gulbagci et al, 2009). Our results suggested the fact that not only DEC2 but also DEC1 is involved in repression of PPARγ2 gene.…”
Section: Dec1 Is Recruited On the Promoter Of Pparγ2mentioning
confidence: 99%
“…Sharp-1, a member of the transcriptional repressor subfamily of basic helix-loop-helix transcription factors, has been shown to be one of the negative regulators in control of C/EBP and PPAR␥ activity. Taneja and co-workers (8) reported that Sharp-1, as a corepressor, inhibits C/EBP activity by retaining HDAC1 and G9a on the C/EBP␣ and PPAR␥2 promoter to inhibit PPAR␥ expression and adipogenesis. Furthermore, Sharp-1 has been shown to be a SUMOylated protein.…”
Section: Discussionmentioning
confidence: 99%
“…This medium was changed every 2 days until the end of differentiation. Oil Red O (Sigma) staining and quantification were performed as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations